Research on enhancing the interactivity of online learning - Wright, Vivian H.; Sunal, Cynthia S.; Wilson, Elizabeth K. (Emerald Publishing Limited : Information Age Pub., 2006)
Our goal with this book, Research on Enhancing the Interactivity of Online Learning, is to present a juried, scholarly, and accessible review of research, theory, and/or policy on specific issues of interactive online learning for K-16 educators, administrators, and students of online learning. Online learning has become the norm rather than the exception for many of today's students. Instructors are more willing to explore online learning options, students are enrolling in record numbers and colleges, as well as many K-12 institutions, are offering more online courses. As educators, we have more tools than ever to ensure online course success, but just as with a traditional class, we must continue to place emphasis on good pedagogy. To achieve good pedagogy, online teaching takes additional time and a restructuring of course content by the instructor. Student issues include coping strategies, ease of navigation, skills required to complete the course, availability of online resources, feedback from the instructor, and collaborative, interactive learning opportunities. Principles of interactive online learning are new to many, and this book provides a forum for interactive online learning research while also including ideas that enhance both the practical and theoretical aspects of interactive online learning. The editors have included chapters that can further knowledge and understanding of emerging trends and foster debate regarding issues that surround interactive online learning.
Keywords: Education -- Computer network resources.; Web-based instruction.; Internet in education.; Education -- Distance, Open & Online Education.; Open learning, distance education.; elektronické knihy; electronic books